Facebook factor in presidential elections in 2014 - Mihai Covaci (Sfera Politicii, 2015)
Elections and presidential campaign from November 2014 have produced in Romania a unique case study. In addition to specific electoral „bait“ of our lands were recovered virtual possibilities offered by current Internet infrastructure. In this occasion, has appeared new concepts in politics area and it was an occasion of historical moment manifestation which must be understood in the context of our living technology era. We witnessed to manifestation of social growing and political consciousness of the Romanians in the country and the Diaspora. Potential voters or those who missed the previous elections should not be ignored. It was a lesson in democracy wave manifested in the virtual environment.